Transcatheter and surgical aortic valve replacement in patients at low surgical risk. Review of major studies - B. S. Tsaroev; A. V. Bogachev-Prokofiev; S. I. Zheleznev; R. M. Sharifulin; A. S. Zalesov; A. M. Chernyavsky (Российский кардиологический журнал)
In recent decades, transcatheter aortic valve replacement (TAVR) has become a revolutionary method for the treatment of severe aortic stenosis, especially for patients at high surgical risk. Studies such as PARTNER and SURTAVI have confirmed the non-inferiority or superiority of TAVR compared with surgical aortic valve replacement in various risk categories. Newer technologies, including third-generation valve systems, have improved durability and reduced complications such as paravalvular regurgitation. However, long-term survival data remain limited, especially for younger patients and groups with anatomical peculiarities. International association guidelines have long favored TAVR for older patients, while surgery remains the preferred option for younger patients with low surgical risk. However, the latter point is increasingly being questioned. The article analyzes key studies, discusses current limitations, and highlights the need for long-term data to inform clinical practice. In conclusion, TAVR is a remarkable achievement in interventional cardiology, but its optimal use requires consideration of individual patient factors.